2010
DOI: 10.1073/pnas.1007583107
|View full text |Cite
|
Sign up to set email alerts
|

Social interaction modulates autonomic, inflammatory, and depressive-like responses to cardiac arrest and cardiopulmonary resuscitation

Abstract: Psychological factors, including depression and social isolation, are important determinants of cardiovascular health. The current study uses a well-validated mouse model of cardiac arrest/cardiopulmonary resuscitation (CA/CPR) to examine the effect of social environment on several pathophysiological and behavioral responses to cerebral ischemia. Male experimental mice were either housed in pairs with an ovariectomized female or socially isolated for the duration of the experiment. Cardiac arrest increased the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
49
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 38 publications
8
49
2
Order By: Relevance
“…Slides were then treated with potassium permanganate (0.06%) for 10 min, rinsed with water, and then incubated in Fluoro-Jade C (0.0001% in a 1% acetic acid solution); sections were rinsed in dH 2 O, and dried on a slide warmer and coverslipped with DPX (Sigma). Consistent with previous studies (Weil et al, 2008(Weil et al, , 2009Norman et al, 2010), Fluoro-Jade C-positive cells were counted in the hippocampus (CA1, CA2, CA3, and dentate gyrus). Images of fluorescently stained sections were captured with a digital camera (Axiocam, Zeiss) connected to a fluorescent microscope (Axioskop, Zeiss) using Axiovision software (Zeiss).…”
Section: Histologysupporting
confidence: 71%
See 1 more Smart Citation
“…Slides were then treated with potassium permanganate (0.06%) for 10 min, rinsed with water, and then incubated in Fluoro-Jade C (0.0001% in a 1% acetic acid solution); sections were rinsed in dH 2 O, and dried on a slide warmer and coverslipped with DPX (Sigma). Consistent with previous studies (Weil et al, 2008(Weil et al, , 2009Norman et al, 2010), Fluoro-Jade C-positive cells were counted in the hippocampus (CA1, CA2, CA3, and dentate gyrus). Images of fluorescently stained sections were captured with a digital camera (Axiocam, Zeiss) connected to a fluorescent microscope (Axioskop, Zeiss) using Axiovision software (Zeiss).…”
Section: Histologysupporting
confidence: 71%
“…For the purposes of histological analysis, another cohort of animals survived for 7 d following either normothermic CA/CPR (n ϭ 10) or control surgeries (n ϭ 15). The control groups consisted of hypothermic CA/CPR (n ϭ 7) and sham (n ϭ 8) animals (see below, CA/CPR procedure, for detailed surgery description); consistent with previous reports (Neigh et al, 2004;Norman et al, 2010), the sham and hypothermic groups did not differ from one another on any of the dependent measures and were subsequently collapsed into a single control group for statistical comparisons. An additional 20 mice (control, n ϭ 10; normothermic CA/CPR, n ϭ 10) survived for 7 d following surgery for analysis of choline acetyltransferase (ChAT) enzymatic activity.…”
Section: Experimental Protocolsmentioning
confidence: 68%
“…Specifically, rodent experiments have demonstrated that the negative effects of social isolation on cerebral ischemia include an increased neuroinflammatory response, greater neuronal death, and impaired functional recovery (Craft, et al 2005; Weil, et al 2008; Norman, et al 2010a; Venna, et al 2012; Karelina, et al 2011). These detrimental effects are likely linked to increased ischemia-induced activation of microglia among socially isolated mice relative to socially integrated mice (Weil, et al 2008; Karelina, et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Activated microglia can secrete pro-inflammatory cytokines and produce reactive oxygen species (Hanish, 2002; Block, et al 2007; Iadecola and Anrather, 2011). Specifically, following cerebral ischemia, gene expression of tumor necrosis factor alpha (TNF-α), interleukin 1 beta (IL-1β), interleukin 6 (IL-6), and nuclear factor kappa b (Nfκb) are significantly upregulated, indicating a pro-inflammatory response (Schneider, et al 1999; Stephenson, et al 2000; Norman, et al 2010a; Doll, et al 2014). Generally, increased post-ischemic neuroinflammation is associated with increased cell death and worse neurological outcome (Wang and Shuaib, 2002; Weil, et al 2008; Neigh, et al 2009; Norman, et al 2010a; Stuller, et al 2012; Doll, et al 2014; Wang, et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation